Schweigen auf Anfrage zur Untervermietung. - (:unkn) unknown (Werner, 2001)
OLG Koblenz, Rechtsentscheid vom 30.4.2001 4 W-RE 525/00. difu
Keywords: Mietrecht; Mietvertrag; Mietwesen; Vermieter; Mieter; Kündigung; Untervermietung; Mieterkündigung